2012
DOI: 10.1159/000334722
|View full text |Cite
|
Sign up to set email alerts
|

Natalizumab May Improve Cognition and Mood in Multiple Sclerosis

Abstract: Immunomodulating therapies may prevent relapses in multiple sclerosis and stabilize neurological status. However, little is known about the influence particularly of newer drugs on cognitive functions. We conducted an open-label prospective study to demonstrate whether natalizumab is apt to improve cognitive functions and mood in 29 patients tested psychometrically while under treatment for 6 months. We found improvements in some measures of attention, memory, mood, and well-being, but no deterioration, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…30 In addition, an open-label study showed that after 6 months of natalizumab therapy, patients demonstrated improved test scores on four of six different cognitive tests, with no deterioration in any test, despite disease duration of more than 10 years. 27 Our results using ANAM, a sensitive measure of multiple cognitive skills, support and extend these observations that cognitive function may be maintained and potentially improved with natalizumab. Because of potential practice effects with With natalizumab therapy, patients experienced significant improvements in fatigue, as measured by three patient-reported scales, and the improvements that were observed during the first 12 weeks of treatment were maintained for up to 48 weeks of treatment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…30 In addition, an open-label study showed that after 6 months of natalizumab therapy, patients demonstrated improved test scores on four of six different cognitive tests, with no deterioration in any test, despite disease duration of more than 10 years. 27 Our results using ANAM, a sensitive measure of multiple cognitive skills, support and extend these observations that cognitive function may be maintained and potentially improved with natalizumab. Because of potential practice effects with With natalizumab therapy, patients experienced significant improvements in fatigue, as measured by three patient-reported scales, and the improvements that were observed during the first 12 weeks of treatment were maintained for up to 48 weeks of treatment.…”
Section: Discussionsupporting
confidence: 81%
“…[26][27][28][29][30] A large Swedish study demonstrated a significant increase in mean Symbol Digit Modalities Test score at 2 years over baseline in natalizumab-treated relapsing-remitting MS patients. 26 A follow-up analysis comparing AFFIRM patients treated with natalizumab with those treated with placebo showed a significant improvement in Paced Auditory Serial Addition Test score at 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, treatment with natalizumab improved EDSS scores mainly in patients who had relapse-mediated worsening of EDSS 22. In addition, other studies also demonstrated an effect of treatment, with natalizumab improving visual acuity,23 visual evoked potential sum scores,24 and cognitive performance 2527. In a small, prospective, magnetic resonance imaging (MRI) study,28 it was found that treatment with natalizumab over 2 years reduced cortical lesions and cortical atrophy when compared with untreated patients and patients treated with first-line therapies.…”
Section: Efficacy Of Natalizumab and Impact On Quality Of Lifesupporting
confidence: 70%
“…Lang and colleagues found stabilizing and improving effects of natalizumab on a selection of memory and attention tests, including PASAT [Lang et al 2012]. Wilken and colleagues observed a stabilization or improvement in computer-based assessed cognitive functions over 1 year in patients treated with natalizumab [Wilken et al 2013].…”
Section: Discussionmentioning
confidence: 99%